Piriformospora indica alleviates soda saline-alkaline stress in Glycine max by modulating plant metabolism - Zhu, Siyu; Shi, Feng; Li, Honghe; Ding, Yiwen; Chang, Wei; Ping, Yuan; Song, Fuqiang (Frontiers in Plant Science, 2024)
Soil salinization is one of the major factors limiting agricultural production. Utilizing beneficial microorganisms like Piriformospora indica (P. indica) to enhance plant tolerance to abiotic stresses is a highly effective method, but the influence of P. indica on the growth of soybean in natural salinealkaline soil remains unclear. Therefore, we investigated the effects of non-inoculation, Pi inoculation, and fertilization on the growth, antioxidant defense, osmotic adjustment, and photosynthetic gas exchange parameters of soybean under two different levels of saline-alkaline stress in non-sterilized natural saline-alkaline soil. The study found that: 1) P. indica inoculation significantly promoted soybean growth, increasing plant height, root length, and biomass. Under mildly saline-alkaline stress, the increases were 11.5%, 16.0%, and 14.8%, respectively, compared to non-inoculated treatment. Under higher stress, P. indica inoculation achieved the same level of biomass increase as fertilization, while fertilization only significantly improved stem diameter. 2) Under saline-alkaline stress, P. indica inoculation significantly increased antioxidant enzyme activities and reduced malondialdehyde (MDA) content. Under mildly stress, MDA content was reduced by 47.1% and 43.3% compared to non-inoculated and fertilized treatments, respectively. Under moderate stress, the MDA content in the inoculated group was reduced by 29.9% and 36.6% compared to non-inoculated and fertilized treatments, respectively. Fertilization only had a positive effect on peroxidase (POD) activity. 3) P. indica inoculation induced plants to produce more osmotic adjustment substances. Under mildly stress, proline, soluble sugars, and soluble proteins were increased by 345.7%, 104.4%, and 6.9%, respectively, compared to non-inoculated treatment. Under higher stress, the increases were 75.4%, 179.7%, and 12.6%, respectively. Fertilization had no significant positive effect on proline content. 4) With increasing stress, soybean photosynthetic capacity in the P. indica-inoculated treatment was significantly higher than in the non-inoculated treatment, with net photosynthetic rate increased by 14.8% and 37.0% under different stress levels. These results indicate that P. indica can enhance soybean's adaptive ability to saline-alkaline stress by regulating ROS scavenging capacity, osmotic adjustment substance content, and photosynthetic capacity, thereby promoting plant growth. This suggests that P. indica has great potential in improving soybean productivity in natural saline-alkaline soils.